An evaluation of unusual warm mix asphalts produced with wax additives - Silva, Hugo Manuel Ribeiro Dias da (2011)
There are several technologies to produce Warm Mix Asphalts (WMA), namely by using water, surfactants, and organic or wax additives to affect the temperature reduction. A particular wax additive (Sasobit®) was studied in this work, which reduces the viscosity of the binder above 100 °C, while notably increases the stiffness at operating temperatures. The main objective of this study was to assess whether it would be possible to produce both high modulus (HMBM) and high flexibility (HFBM) bituminous mixtures by adding a wax to base bitumens softer than those normally applied in such mixtures (i.e. 35/50 wax modified bitumen vs. 10/20 pen bitumen – HMBM, and 160/220 wax modified bitumen vs. 50/70 pen bitumen – HFBM). The optimum additive content and the reduction of temperature were selected based on the properties of the binders. Finally, performance tests were carried out on the studied mixtures, being possible to conclude that the use of waxes reduced the production temperature of both WMA mixtures by 30 40 ºC, maintaining or even improving some properties of those mixtures.